Outcomes of Alzheimer's disease therapy with acetylcholinesterase inhibitors and memantine. (June 2014) - Zemek, Filip; Drtinova, Lucie; Nepovimova, Eugenie; Sepsova, Vendula; Korabecny, Jan; Klimes, Jiri; Kuca, Kamil
Abstract : Introduction: Alzheimer's disease (AD) is a world-wide health problem with implications for an increasing number of people and countries. Populations suffering from AD financially strain the healthcare budgets of rich and poor countries alike. Moreover, no effective treatment is available and current drugs merely slow the progression of cognitive function deterioration and overall health status toward an inevitable end point. An increasing number of novel approaches have been tested in numerous clinical trials, but none of them has proved safe and effective for treating AD. Areas covered: This review summarizes all currently available compounds (donepezil, rivastigmine, galantamine, memantine) for the management of AD, concentrating on clinical aspects such as the mechanisms of action, pharmacokinetics, pharmacodynamics and clinical trials. This review also considers the mechanisms and side effects to provide perspective on current treatment options. Expert opinion: Novel approaches in the treatment of AD are being intensively tested, but so far without any major success. Patients diagnosed with AD still mostly benefit from four compounds to significantly improve cognition functions and overall health and help manage other symptoms or even prolong the symptom-free period.